2008
DOI: 10.1007/s00432-008-0454-7
|View full text |Cite
|
Sign up to set email alerts
|

Randomised trial comparing biweekly oxaliplatin plus oral capecitabine versus oxaliplatin plus i.v. bolus fluorouracil/leucovorin in metastatic colorectal cancer patients: results of the Southern Italy Cooperative Oncology study 0401

Abstract: Purpose Oxaliplatin combined with either Xuorouracil/ leucovorin (OXAFAFU) or capecitabine (OXXEL) has a demonstrated activity in metastatic colorectal cancer patients. We aimed at comparing these two regimens in terms of response rate (RR), safety, progression-free survival (PFS), and quality of life (QoL) of patients. Methods A total of 322 patients with metastatic colorectal cancer were randomized to receive biweekly: oxaliplatin 100 mg/m 2 i.v. on day 1, capecitabine 1,000 mg/m 2 orally twice daily from da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 36 publications
(28 reference statements)
2
26
0
Order By: Relevance
“…Two of the ten trials Kohne et al 2008) included other treatment arms, in addition to the two arms considered for the meta-analysis. In combination settings, capecitabine dose was 1,000 mg/m 2 .bid d 1-11 in one trial (Comella et al 2009), 1,000 mg/m 2 .bid d 1-14 in six trials Diaz-Rubio et al 2007;Kohne et al 2008;Martoni et al 2006;Porschen et al 2007;Rothenberg et al 2008), and 1,000 mg/m 2 .bid d 2-15 in one trial (Skof et al 2009). …”
Section: Selection Of the Trialsmentioning
confidence: 98%
See 1 more Smart Citation
“…Two of the ten trials Kohne et al 2008) included other treatment arms, in addition to the two arms considered for the meta-analysis. In combination settings, capecitabine dose was 1,000 mg/m 2 .bid d 1-11 in one trial (Comella et al 2009), 1,000 mg/m 2 .bid d 1-14 in six trials Diaz-Rubio et al 2007;Kohne et al 2008;Martoni et al 2006;Porschen et al 2007;Rothenberg et al 2008), and 1,000 mg/m 2 .bid d 2-15 in one trial (Skof et al 2009). …”
Section: Selection Of the Trialsmentioning
confidence: 98%
“…1), ten eligible trials Comella et al 2009;Diaz-Rubio et al 2007;Hoff et al 2001;Kohne et al 2008;Martoni et al 2006;Porschen et al 2007;Rothenberg et al 2008;Skof et al 2009;Van Cutsem et al 2001) were identified, and the respective electronic databases were obtained for all of them. The quality scores of the RCTs were assessed according to the Jadad scale (Jadad et al 1996) and ranged from 2 to 4 (5-point scale), with a mean of 3.3.…”
Section: Selection Of the Trialsmentioning
confidence: 99%
“…Of the studies included in Amgen's NMA [n = 21, reported in 22 publications 28 [78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94] The reason for their exclusion was that they did not evaluate the effectiveness of the interventions in the RAS WT population. In addition to the abstracts for the OPUS 33 and CRYSTAL 34 trials included in the Amgen NMA, the Assessment Group identified the full publications.…”
Section: Comparison With the Assessment Group's Network-meta-analysismentioning
confidence: 99%
“…Available quality-of-life data suggest that there are no differences between capecitabine and 5-FU-based regimens [71,72]. A study by Liu et al [73] suggests that patients prefer oral chemotherapy, provided that efficacy is not compromised.…”
Section: Pharmacoeconomics and Patient Considerationsmentioning
confidence: 97%